If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 + -1(7x + -1(12(x + -1) + -5)) = 5(x + -3) Reorder the terms: 2x + 10 + -1(7x + -1(12(-1 + x) + -5)) = 5(x + -3) 2x + 10 + -1(7x + -1((-1 * 12 + x * 12) + -5)) = 5(x + -3) 2x + 10 + -1(7x + -1((-12 + 12x) + -5)) = 5(x + -3) Reorder the terms: 2x + 10 + -1(7x + -1(-12 + -5 + 12x)) = 5(x + -3) Combine like terms: -12 + -5 = -17 2x + 10 + -1(7x + -1(-17 + 12x)) = 5(x + -3) 2x + 10 + -1(7x + (-17 * -1 + 12x * -1)) = 5(x + -3) 2x + 10 + -1(7x + (17 + -12x)) = 5(x + -3) Reorder the terms: 2x + 10 + -1(17 + 7x + -12x) = 5(x + -3) Combine like terms: 7x + -12x = -5x 2x + 10 + -1(17 + -5x) = 5(x + -3) 2x + 10 + (17 * -1 + -5x * -1) = 5(x + -3) 2x + 10 + (-17 + 5x) = 5(x + -3) Reorder the terms: 10 + -17 + 2x + 5x = 5(x + -3) Combine like terms: 10 + -17 = -7 -7 + 2x + 5x = 5(x + -3) Combine like terms: 2x + 5x = 7x -7 + 7x = 5(x + -3) Reorder the terms: -7 + 7x = 5(-3 + x) -7 + 7x = (-3 * 5 + x * 5) -7 + 7x = (-15 + 5x) Solving -7 + 7x = -15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 7x + -5x = -15 + 5x + -5x Combine like terms: 7x + -5x = 2x -7 + 2x = -15 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + 2x = -15 + 0 -7 + 2x = -15 Add '7' to each side of the equation. -7 + 7 + 2x = -15 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = -15 + 7 2x = -15 + 7 Combine like terms: -15 + 7 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 7p-(3p+4)=-2p-1+10 | | 30+18x=21.54 | | 20x^3+100x^2=0 | | 34x-16+15x^2=0 | | 9x+10=-2(x+3)+3x | | r^4=3r^3+18r^2 | | 10x+8=65+13x | | y^2=x+1 | | 12=-14B+3B | | 0.14-0.01(x-2)=-0.02(3-x) | | X-x(3x-5)=x-2(x(x)+x)-x(x)-14 | | S=2(3.14)rh+(3.14) | | y=14-2y | | -6-3=9r-6 | | 0.10(x+10)+0.70x=17 | | 4(2x-5)=3x+13 | | 10P+8=5P-2 | | 13-22=-3x | | 16-3b=0 | | 5=7Y-5Y-3 | | y^2+13y+12= | | 16-36=0 | | 10B-11B=0 | | 2(-4+p)=-8.2+1.8p | | -4=-9+8-29 | | x^2+47x+56=0 | | H(x)=2x^3+5x^2-31x-15 | | -15n^2+13=-10n^2-6n | | 6x(3x-4)(2x+5)= | | x^6-243=0 | | -4=9+8-29 | | 3n^2=-8 |